Des-atando os nós : a violência sexual na Internet nos sentidos atribuídos pelos jovens - Fávero, Rutinelli da Penha (2009)
The frequency of the spreading of events related to the sexual violence in the media, the use of images and infantile or youthful videos for pornographic ends, as well as the news of allurement of children and young, the “assented” involvement of adolescents with adults for sexual ends initiated from the Internet, and all the other forms of sexual violence against children and adolescents in the Internet are more and more apparent. From this reality, the objectives of this work are: to give voice to the young about the meanings they attribute to the sexual violence, in special that one that presents itself in the Internet; beyond questioning if it is possible that by means of the relations established for the young, either through the resources of the Net, either through the relationships established in presentably , that practices may be built of which the education can make use for the confrontation or the prevention of the sexual violence. This research has fenomenological inspiration and uses the technique of group of focus for the attainment material for the study. The group was carried through with youngsters of the Professional Education of High School Level, for reflection, questioning, survey of the opinions and report of the experiences of the related thematic. In a school institution like Ifes, knowledge and technique are very important and they are valued by the pupils for their future professional performances, however, this certainty does not hinder the young of understanding the school as much more that a place of technique only. The technological transformations generate changes caused mainly for the modifications in the relations and, the Internet serves to the young, beyond the daily uses of research and leisure, as a resource to initiate them, to keep or to deepen relations by the resources of the Net itself. There are left notes of the possibility to construct learning relations that include a more ethical, however, not without flavor and joy existence; more religious e, in a return to our common feelings and in spirituality that in link we back to ourselves and to the ones we’re surround by (KIERKEGAARD, 1859/1986). Some possibilities are: to invest in the creation of nets of support and cooperation between these youngsters, virtual communities mediated by the professors and the youngsters themselves, place for discussion of the specific thematic raised by the youngsters in lists of discussions or sites of relationships, among others resources to be built along with the youngsters in their attributions of meanings